PENGARUH HARGA CITRA MEREK DAN FITUR TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE VIVO OLEH PEGAWAI DAN SISWA DI SMA NEGERI 2 MUARA BADAK - FATIMAH, NURUL; JOHANSYAH, JOHANSYAH (I-Con Media, 2021)
Digitalization and rapid development in technology have been changing customers’needs and wants, including the needs for telecommunication tools. It creates new challenges and fierce competition for smartphone makers. The purpose of this study is to determine the effect of price, brand image and features simultaneously and partially on purchase decisions for Vivo smartphones. The respondents for this study were 106 employees and students of SMA Negeri 2 Muara Badak.. The analytical tool used is multiple regressions and testing the research hypothesis using the F test and t test.Simultaneously, it shows that price, brand image and features have a significant influence on purchasing decisions on purchase decision. Partially it shows that price, brand image and features positively and significantly affect purchase decisions with a value of Fcount 8,496> F table 2.70. The most influential variabel in this study is Price with t count 6.115> t table 1.659. It implies that price still becomes the strongest predictor for students and teachers when deciding to purchase a smartphone.